SELECTION OF THE PREFERRED DESIGN FOR MANUFACTURABILITY BY CONSTRUCTING THE PARETO TUPLE - Irzaev, Gamid; Kanaev, Magomedimin; Isalova, Marzhanat (Journal of Applied Engineering Science, 2021)
The system to ensure manufacturability of industrial products is aimed at reducing the costs of all types of resources at the stages of their life cycle, selecting the most competitive in cost and functionality designs at the early stages of engineering. When assessing the new designs for manufacturability to be developed and selecting the best analogue or basic reference standard in terms of manufacturability, the engineer faces the need to apply multicriteria optimization methods. The solution of the applied task of design optimization by quantitative criteria of manufacturability in the conditions of an uncertain design and production environment is considered in the article as implementable in the system for ensuring design for manufacturability. The decisive rules for implementing the multi-step process of ranking the design options according to the manufacturability criteria with the construction of the Pareto tuple are formed. The implementation of the method is exemplified in practice when choosing the oscilloscope design that is advantageous in terms of manufacturability at a mass-production instrument-making plant.